2020
DOI: 10.3390/molecules25030461
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Flavor Compounds in Cheese as Affected by Ruminant Diet

Abstract: Extensive research has been conducted concerning the determination and characterization of volatile compounds contributing to aroma and flavor in cheese. Considerable knowledge has been accumulated on the understanding of the mechanisms through which these compounds are formed during ripening, as well as on the optimization of the methodological approaches which lead to their detection. More recently, particular attention has been given to the aromatic properties of milk and cheeses obtained from lactating dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 73 publications
2
29
0
2
Order By: Relevance
“…Both compounds are generally produced for the catabolism of free amino acids contributing to the odor profile. Sulphur and amine compounds are reported to be characterized by a low odor threshold perception, thus markedly influencing the cheese flavor and they make a significant contribution to the cheese typical flavor [ 67 , 68 , 69 ]; the different concentration of these compounds could vary in relation to the animal diet [ 70 , 71 ]. This in agreement with Castellani et al (2018) [ 72 ] that affirmed that in dairy cows, dietary supplementation of dried olive pomace may affect proteolytic volatile compounds in milk and cheese.…”
Section: Discussionmentioning
confidence: 99%
“…Both compounds are generally produced for the catabolism of free amino acids contributing to the odor profile. Sulphur and amine compounds are reported to be characterized by a low odor threshold perception, thus markedly influencing the cheese flavor and they make a significant contribution to the cheese typical flavor [ 67 , 68 , 69 ]; the different concentration of these compounds could vary in relation to the animal diet [ 70 , 71 ]. This in agreement with Castellani et al (2018) [ 72 ] that affirmed that in dairy cows, dietary supplementation of dried olive pomace may affect proteolytic volatile compounds in milk and cheese.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the evaluation of volatile profile, it is important to underline the fact that, in recent years, numerous studies on ruminants highlighted the influence of the feeding strategy to induce variations in the release of VOCs in milk and derived dairy products [34]. In our study, free fatty acids (FFAs) represent the most abundant class of compounds found in fresh (T1) and ripened (T60) samples, testifying for the prevalence of the lipolytic processes compared to the proteolytic events.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely observed that the diet administered to lactating ruminants is commonly responsible for changes in the volatile profile of dairy products, both fresh and ripened [113][114][115][116]. It is, therefore, conceivable that compounds present in the diet, or secondary metabolites of the same, can be absorbed by the animal following digestion and then reach the mammary gland and be released into the milk.…”
Section: Volatile Flavor Compounds and Sensorial Evaluationsmentioning
confidence: 99%